Thermal annealing effects on silver nanowire networks. (1st January 2014) - Giusti, G.; Langley, D.P.; Lagrange, M.; Collins, R.; Jimenez, C.; Bréchet, Y.; Bellet, D.
Thermal annealing is shown to be a successful approach to reduce the electrical resistance of transparent electrodes made of randomly oriented silver nanowires (AgNWs). A decrease in the electrical resistance by several orders of magnitude, whilst maintaining optical transmission (above 85%), is demonstrated. Several mechanisms involved in the electrical behaviour induced by thermal treatment both in air and under vacuum are identified using a combination of ramped, stepped and isothermal annealing. Some mechanisms lead to the reduction of the electrical resistance such as local sintering, while others, such as spheroidisation, induce irreversible damage to the network. It is also shown that the polymer used in the synthesis of Ag nanowires plays a crucial role as a thermal stabiliser under vacuum conditions. Finally, optimised samples exhibit an optical transmittance of 83% (without substrate contribution removal) and a sheet resistance of 9.5 Ω/sq.